Language, migration, and identity : neighborhood talk in Indonesia - Goebel, Zane. (Cambridge : Cambridge University Press, 2010)
'While much scholarship has been devoted to the interplay between language, identity and social relationships, we know less about how this plays out interactionally in diverse transient settings. Based on research in Indonesia, this book examines how talk plays an important role in mediating social relations in two urban spaces where linguistic and cultural diversity is the norm and where distinctions between newcomers and old timers changes regularly. How do people who do not share expectations about how they should behave build new expectations through participating in conversation? Starting from a view of language-society dynamics as enregisterment, Zane Goebel synthesizes a wide range of humanities scholarship with contemporary linguistic anthropology to explore how language is used in this contact setting to build and present identities, expectations and social relations. It will be welcomed by researchers and students working in the fields of linguistic anthropology, sociolinguistics, the anthropology of migration and Asian studies'--
Machine generated contents note: 1. Introduction; 2. Long term processes of enregisterment; 3. Enregistering local practices and local spaces; 4. Linguistic signs, alternation, crossing and adequation; 5. Women, narratives, identity and expectations in ward 8; 6. Learning to become a good ward member; 7. Emerging identities in a monthly ward 8 male meeting; 8. Chineseness as deviance; 9. Language ideologies and practice in ward 5; 10. Conclusions.
Includes bibliographical references (p. 202-213) and index.
Keywords: Anthropological linguistics -- Indonesia -- Semarang; Sociolinguistics -- Indonesia -- Semarang; Ethnicity -- Indonesia -- Semarang; Language and culture -- Indonesia -- Semarang; Communication and culture -- Indonesia -- Semarang; Semarang (Indonesia) -- Ethnic relations; Semarang (Indonesia) -- Social life and customs